The Effect of a Fall Proof Training on Balance and Fear of Falling in Older Women - Ebrahim Mohammad Ali Nasab Firouzjah; Leila Farnian (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Balance deficiency is one of the risk factors for falls, injury or even death of the elderly. This study aimed to investigate The Effect of a Fall Proof training on balance and fear of falling in older women was conducted. Methods This study was a quasi-experimental study with a pretest-posttest design. Thirty elderly women aged 60-70 years were selected as available for the sample. Subjects were randomly divided into control (n=15) and experimental (n=15) groups. To assess static and dynamic balance, Sharpend Romberg test and time up and go test and to assess fear of falling the fear of falling questionnaire were used. Exercises were performed for 8 weeks, three sessions per week and each session for 60 minutes by experimental group, while the control group did not do any exercise. Analysis of covariance and paired t-test were used to analyze the dataResults The results of this study showed that a period of Fall Prof Training significantly increased static (P=0.01) and dynamic balance (P=0.01) and a significant decrease in fear of falling (P=0.01) In the experimental group compared to the control group.Conclusion Due to the weak balance and high fear of falling in the elderly, based on the findings of this study, we can use fall proof exercises in elderly rehabilitation and exercise.